ANALISIS PENGGUNAAN TEKNOLOGI INFORMASI DIGITAL DALAM PELAYANAN PUBLIK DI KELURAHAN KARAWANG KULON - Sukma, Gina Laelita; Syam, Guruh Ramdhan Hasbillah; Azijah, Dewi Noor (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2024)
Today's technology has penetrated everywhere, even today humans cannot live without technology. For example, information technology is needed by the community in communicating, for example. Not inferior to other fields, the government also uses technology in work and service systems called e-government. The concept of e-government adheres to the concept of e-governance, the aspects that exist in this governance are reflected in e-government. This study uses a qualitative descriptive type with data analysis by Miles and Huberman. This research was conducted in the Village of Karawang Kulon. Based on the results of e-government research, Karawang Kulon Village has not used e-government at all. manuals. So that the Karawang Kulon Village has not been able to prepare e-government because there has been no order from West Karawang District.